2008
DOI: 10.1002/art.24003
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity of rheumatoid arthritis during pregnancy: Results from a nationwide prospective study

Abstract: Objective. According to common knowledge and retrospective studies, approximately 75-90% of patients with rheumatoid arthritis (RA) will improve during pregnancy. Prospective data on disease activity during pregnancy are limited. Therefore, this study aimed to prospectively determine the disease activity during pregnancy in RA patients treated in an era of new treatment options. Methods. For 84 RA patients (American College of Rheumatology criteria), a Disease Activity Score in 28 joints (DAS28) and medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
299
0
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 455 publications
(331 citation statements)
references
References 13 publications
14
299
0
18
Order By: Relevance
“…Up to half of pregnant patients with rheumatic diseases and the majority of those with inflammatory bowel disease (IBD) experience active disease and need treatment 3, 4. High disease activity is associated with an increased risk of pregnancy complications and adverse outcomes, including preeclampsia, preterm delivery, low birth weight, small for gestational age, and fetal loss 5, 6, 7, 8, 9, 10, 11, 12, 13. Adequate disease control during pregnancy is therefore paramount for fetal and maternal health, as acknowledged by recent publications 6, 14, 15, 16, and the risks of untreated disease during pregnancy should be evaluated against the risks related to drug exposure of mother and fetus.…”
mentioning
confidence: 99%
“…Up to half of pregnant patients with rheumatic diseases and the majority of those with inflammatory bowel disease (IBD) experience active disease and need treatment 3, 4. High disease activity is associated with an increased risk of pregnancy complications and adverse outcomes, including preeclampsia, preterm delivery, low birth weight, small for gestational age, and fetal loss 5, 6, 7, 8, 9, 10, 11, 12, 13. Adequate disease control during pregnancy is therefore paramount for fetal and maternal health, as acknowledged by recent publications 6, 14, 15, 16, and the risks of untreated disease during pregnancy should be evaluated against the risks related to drug exposure of mother and fetus.…”
mentioning
confidence: 99%
“…More than one-half of the mothers in this study were taking a medication for RA during pregnancy, but only one-fifth used a combination of medication. In addition, studies have demonstrated that low disease activity during conception is relevant to the maintenance of stable, low disease activity during pregnancy (8,17). Others have shown that pregnant women with RA who discontinued their medications during pregnancy had worse outcomes, in terms of preterm delivery, than did women who continued their medications (18).…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort consisted of 255 healthy children of mothers who participated in the Pregnancyinduced Amelioration of Rheumatoid Arthritis (PARA) study, a prospective, nationwide cohort study on pregnancy and RA in The Netherlands that started in 2002 and ended in 2010 (8). Women were recruited by their rheumatologist when they met the American College of Rheumatology 1987 revised criteria for RA (10) and were eligible for inclusion if they were planning to conceive or were already pregnant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recognized that pregnant patients with rheumatoid arthritis can often undergo significant clinical improvement, followed by worsening disease after delivery [66][67][68][69]. This observation, in fact, helped lead Hench to the discovery of corticosteroids as the first treatment for RA [70].…”
Section: T Regulatory Cellsmentioning
confidence: 99%